Early Heatstroke Risk Detection for Children with IoT Technology - Normahisham, Norazura Syairah; Yahya @ Atan, Roshayati (Evolution in Electrical and Electronic Engineering, 2023)
Heatstroke is a medical emergency that may cause brain damage and other internal organ failure. It is caused by overheating, which usually occurs when a person lacks sweating while doing activities or is exposed for a long period to high surrounding temperatures with low humidity. This device measure and monitor the body temperature, sweating rate, heart rate, oxygen saturation (SpO2), the surrounding temperature, and humidity, as a result, heat stroke level risk will be generated through the Durian UNO with ESP8266 microcontroller and notify the User through Blynk application as for the IoT part. Based on the result, it can be concluded that the device is capable of detecting heat stroke risk and alerting the user before any heat stroke occurrence. The device can detect heat stroke risk with an accuracy ranging from 98.46% to 99.87%, providing early alerts to prevent heat stroke occurrences.